Measurement in tribal Aboriginal communities - Harris, Pamela Joan (Northern Territory Dept. of Education, 1980)
Maths in Aboriginal society; teaching maths in Aboriginal schools; maths in English and bilingual instruction; research design for study of Aboriginal use of maths; concepts of measurement based on study of NT communities.